Pulmonary metastasis secondary to abiraterone‐resistant prostate cancer with homozygous deletions of BRCA2: First Japanese case. Issue 1 (15th October 2020) - Izawa, Mizuki; Kosaka, Takeo; Nakamura, Kohei; Oba, Junna; Hishida, Tomoyuki; Hongo, Hiroshi; Mikami, Shuji; Nishihara, Hiroshi; Oya, Mototsugu
Abstract : Introduction: Most metastatic prostate cancers acquire the capacity for androgen‐independent growth and become resistant to androgen deprivation therapy. A patient‐focused treatment strategy is needed for aggressive castration‐resistant prostate cancer. Case presentation: We report the case of a 62‐year‐old man who presented with prostatic adenocarcinoma who was treated by radiation and combined androgen blockade. After completion of first‐line therapy, he was diagnosed with multiple metastatic castration‐resistant prostate cancer in the lung. Second‐line therapy with abiraterone acetate resulted in partial remission of the lung metastases. Thoracic surgery was performed to remove the single lung metastasis remaining. Next‐generation sequencing of the specimens demonstrated homozygous loss of BRCA2 . We note in this case a heterogeneous response to abiraterone acetate may be related to the somatic BRCA2 deletions. Conclusions: We present the first Japanese case of a metastatic abiraterone acetate‐resistant castration‐resistant prostate cancer accompanied by BRCA2 mutation.